1974
DOI: 10.1177/030098587401100202
|View full text |Cite
|
Sign up to set email alerts
|

A Toxic Cardiomyopathy Caused byCassia occidentalis. II. Biochemical Studies in Poisoned Rabbits

Abstract: Abstract. Mitochondrial damage was evident in the earliest lesions in cardiac muscle of rabbits poisoned by coffee senna (Cassia occidentalis), suggesting that mitochondria might be the target for the toxic action of coffee senna. Oxidative phosphorylation by mitochondria isolated from poisoned rabbits was uncoupled, and in more severely affected rabbits mitochondrial respiration was depressed. The activities of myocardial malic dehydrogenase, isocitric dehydrogenase and lactic dehydrogenase were increased, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…O'Hara and Pierce found (O'Hara and Pierce, 1974a) that seeds of C. occidentalis induced uncoupling of oxidative phosphorylation and depressed respiration in mitochondria isolated from the heart of poisoned rabbits. Other biochemical studies of mitochondrial particles of chicken liver demonstrated lower phosphorylation ratios, and lower rates of oxygen use (Graziano et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…O'Hara and Pierce found (O'Hara and Pierce, 1974a) that seeds of C. occidentalis induced uncoupling of oxidative phosphorylation and depressed respiration in mitochondria isolated from the heart of poisoned rabbits. Other biochemical studies of mitochondrial particles of chicken liver demonstrated lower phosphorylation ratios, and lower rates of oxygen use (Graziano et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The exact Cassia seed toxins in natural or experimental cases are unknown [1,5,13,15,16,18,21,23,24]. Alkaloids and triterpens have been found in liver and muscle samples from cattle poisoned by C. occidentalis seeds [8].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical cases have been anecdotally mentioned in horses but frequently lack a detailed description [14]. Experimental intoxication has been demonstrated in cattle [13,18], goats [3,19], chickens [4,5,20,21], rats [1,22], rabbits [12,23,24] and horses [25,26]. Experimentally poisoned horses are severely ataxic and may die acutely without showing any clinical signs.…”
Section: Introductionmentioning
confidence: 99%